Artificial intelligence applications and innovations : 14th IFIP WG 12.5 International Conference, AIAI 2018, Rhodes, Greece, May 25-27, 2018, Proceedings /: 14th IFIP WG 12.5 International Conference, AIAI 2018, Rhodes, Greece, May 25-27, 2018, Proceedings. (2018) - Unknown
No abstract available